Factors related to psychological impairment and quality of life in patients with schizophrenia - Machado,Fernanda Pâmela (2021)
ABSTRACT Objective: to describe the factors related to psychological impairment and quality of life (QoL) of patients with schizophrenia. Method: a cross-sectional, descriptive and correlational study, carried out with 119 schizophrenics. A questionnaire of sociodemographic and clinical variables was applied, plus BPRS-A and QLS-BR scales. Chi-square test and Spearman’s correlation were used, Results: seventy-seven were male and 44 were using typical medications. The “Number of times they were hospitalized” related to “Time of illness” that patients live with schizophrenia showed significance (p=0.266); 91.7% had a severe occupational level (n=109); 34.5% (n=41) had moderate impairment. Conclusion: the greater the degree of psychological impairment, the worse the QoL, this worsening may be related to several factors, as well as disease symptoms.